2019
DOI: 10.1111/1751-2980.12748
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of vedolizumab in patients with inflammatory bowel diseases: A real‐life experience from a tertiary referral center

Abstract: Objective: The study aimed to evaluate the long-term efficacy and safety of vedolizumab in a real-life cohort of patients with inflammatory bowel diseases enrolled at a tertiary referral center.The primary outcomes were clinical response and remission at 14, 24, and 52 weeks, and steroid-free remission rate (SFRR) at 52 weeks. Endoscopic response and remission rates at 52 weeks were the secondary outcomes. Results: Altogether 49 patients (22 with ulcerating colitis [UC] and 27 with Crohn'sDisease [CD]) were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…Canadian and Hungarian real-world cohorts also showed signi cantly greater clinical remission and response rate for UC compared with CD [31,32]. However, opposite results reported by Gabriele et al, cohort in Italy showed better results for CD patients, with higher clinical response and remission rate compared with UC at 14 weeks (85% and 69% vs. 52% and 30%), 24 weeks (84% and 61% vs. 56% and 26%) and 52 weeks (59% and 45% vs. 25% and 20%) [33]. The difference in clinical response and remission rate could be attributed to quite small sample size and differences in patients baseline characteristics variability: the characteristic of patients involved varied in IBD phenotype, disease severity at vedolizumab initiation, disease duration.…”
Section: Discussionmentioning
confidence: 74%
“…Canadian and Hungarian real-world cohorts also showed signi cantly greater clinical remission and response rate for UC compared with CD [31,32]. However, opposite results reported by Gabriele et al, cohort in Italy showed better results for CD patients, with higher clinical response and remission rate compared with UC at 14 weeks (85% and 69% vs. 52% and 30%), 24 weeks (84% and 61% vs. 56% and 26%) and 52 weeks (59% and 45% vs. 25% and 20%) [33]. The difference in clinical response and remission rate could be attributed to quite small sample size and differences in patients baseline characteristics variability: the characteristic of patients involved varied in IBD phenotype, disease severity at vedolizumab initiation, disease duration.…”
Section: Discussionmentioning
confidence: 74%
“…Those rates are substantially higher than in the regulatory GEMINI 1 trial [7]. In other real-world studies, remission rates vary widely between 20 and 82.5% [15][16][17][18][19][20][21][22][23][24]. Differences in the characteristics of study populations and/or definitions of outcomes may underlie these discrepancies.…”
Section: Discussionmentioning
confidence: 90%
“…Differences in the characteristics of study populations and/or definitions of outcomes may underlie these discrepancies. Indeed, the lowest rates were reported in studies with the smallest numbers of patients, which may have skewed results toward worse outcomes [17,18,20]. Enrichment with patients reporting multiple anti-TNF failures may be another reason.…”
Section: Discussionmentioning
confidence: 99%
“…38 Although a cardiac death has been reported in a 66-year-old male 14 days after the first induction dose of vedolizumab (an integrin receptor antagonist currently used to treat UC), it should be emphasised that this patient had a 2-year history of chronic ischaemic heart disease, 39 making unlikely that this drug exerted a toxic effect. In this line, the safety of vedolizumab has been well documented both in naive or in patients previously treated with anti-TNF-α agent, [40][41][42][43] and in studies with a long-term follow-up (up to 5 years). 40 44-47 Based on the data emerged by our case report, the first episode of myocarditis could be attributable to MSZ therapy even though it is not possible to rule out a previously misdiagnosed extra-intestinal manifestation of UC perhaps triggered by MSZ.…”
Section: Discussionmentioning
confidence: 99%